Integration of Local Wisdom and Adaptive Public Leadership in Promoting Local Potential-Based Regional Development - Salamun Salamun; Edi Susilo (Journal of Social Science and Humanities, 2026)
This study aims to examine how integrating local wisdom and flexible public leadership fosters successful regional development driven by local potential. The research was conducted in Banyuwangi Regency (East Java), Sleman Regency (Special Region of Yogyakarta), and Badung Regency (Bali)—areas selected for their relatively successful regional development practices in optimizing local potential. A descriptive qualitative approach was employed, with data collected through in-depth interviews with traditional leaders, local government heads, officials, and community members involved in the development process. Secondary data—comprising regional planning and development documents, annual performance and development reports, and official publications from relevant agencies—complemented the primary data. Thematic analysis was used to identify patterns of relationships among local values, leadership characteristics, community engagement, and development sustainability. The findings indicate that the success of development based on local potential depends not merely on the volume of available resources, but primarily on how effectively local governments integrate local cultural values ​​and knowledge into development governance through responsive, collaborative, innovative, and flexible leadership. Patterns observed across all three regions included strengthened community participation, enhanced social resilience, the emergence of context-specific policy innovations, and the maintenance of economic and environmental sustainability. The study demonstrates that the synergy between local wisdom and flexible public leadership is a strategic component in establishing regional development governance that is rooted in local characteristics yet responsive to external dynamics. This integration offers an alternative model for regional development that is more contextual, inclusive, adaptive, and sustainable in the face of global challenges and multidimensional crises.